Polityka delokalizacji produkcji w Unii Europejskiej w warunkach strategicznej rywalizacji Chin i USA. W kierunku nowego kształtu globalnych łańcuchów wartości (Politeja, 2024)
THE POLICY OF RELOCATING PRODUCTION IN THE EUROPEAN UNION IN THE CONTEXT OF THE STRATEGIC RIVALRY BETWEEN CHINA AND THE USA: TOWARD GLOBAL VALUE CHAINS TRANSFORMATIONThe policy of relocating production in the EU is a response to the challenges faced by the global economy. It is also an action in which the EU is trying to respond to the policy of its main economic competitors, i.e., the USA and China. The diagnoses suggest the need for regulators to take action. Therefore, countries are competing to implement measures that are supposed to increase the level of supply security and eliminate possible future disruptions, especially in areas that are considered the most sensitive. The aim of the article is to identify the extent to which EU policy may affect the relocation of production in the EU, and thus the shape of value chains, in the context of increased political uncertainty as a result of the US-China rivalry. This article argues that the EU’s policy of relocating production is aimed at diversifying and increasing the resilience of supply chains by favouring the location of production in the Member States. However, the instruments used by the EU are not fully adequate for the problems that have arisen.